2020
DOI: 10.1111/1759-7714.13631
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of immune checkpoint inhibitor consolidation after chemoradiation in patients of Asian ethnicity with unresectable stage III non‐small cell lung cancer: Chinese multicenter report and literature review

Abstract: Background: The PACIFIC study has defined a new standard of care for patients with unresectable stage III non-small cell lung cancer (NSCLC) in the form of immune checkpoint inhibitor (ICI) consolidation therapy. However, there is little specific data pertaining to the safety and efficacy of this approach in Chinese NSCLC patients. Methods: This was a prospective multicenter cohort study. Between September 2018 and January 2020, patients with unresectable stage III NSCLC that had undergone chemoradiation thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 33 publications
0
11
1
Order By: Relevance
“…Consistently, our results also indicated that V20 was an independent risk factor for occurrence of symptomatic pneumonitis (OR 3.49 p = 0.007; V20 ≥ 16.7% vs. V20 < 16.7%, 67.44% vs. 36.73%). Notably, the cut‐off value of V20 in our analysis was lower than those established in previous studies with range of 20%–35% 15,16,34‐38 . We speculated that this was possibly due to the predisposition of symptomatic pneumonitis in patients receiving TRT after PD‐(L)1 inhibitor treatment, which alerted radiation oncologists to delineate target plan carefully to control total lung V20 in order to minimize the incidence of pneumonitis when chose this sequential regimen.…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…Consistently, our results also indicated that V20 was an independent risk factor for occurrence of symptomatic pneumonitis (OR 3.49 p = 0.007; V20 ≥ 16.7% vs. V20 < 16.7%, 67.44% vs. 36.73%). Notably, the cut‐off value of V20 in our analysis was lower than those established in previous studies with range of 20%–35% 15,16,34‐38 . We speculated that this was possibly due to the predisposition of symptomatic pneumonitis in patients receiving TRT after PD‐(L)1 inhibitor treatment, which alerted radiation oncologists to delineate target plan carefully to control total lung V20 in order to minimize the incidence of pneumonitis when chose this sequential regimen.…”
Section: Discussioncontrasting
confidence: 53%
“…The total lung V20 is a crucial and the most frequently described dosimetric parameter generally used to define a specific threshold dose to predict the occurrence of radiation pneumonitis. 15,16,[34][35][36][37][38] cancer who underwent concurrent chemoradiotherapy and evaluated the association between V20 and symptomatic pneumonitis. 15 The results showed that V20 = 25% was an optimal cut-off value to differentiate patients with high risk for development of symptomatic pneumonitis (OR 1.03, p = 0.008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, surgical resection combined with chemotherapy and radiotherapy is a primary method for treating LUAD [3]. In recent years, lung cancer immunotherapy has become a new research hot spot, which can activate the patients' immune system, exert an antitumor effect [4], and improve the clinical symptoms and overall survival [5]. Despite the advance of immunotherapy, the prognosis of patients with LUAD remains poor [6].…”
Section: Introductionmentioning
confidence: 99%